Low Self-Confidence and Diabetes Mismanagement in Youth with Type 1 Diabetes Mediate the Relationship between Behavioral Problems and Elevated HbA1c - Minke M. A. Eilander; Maartje de Wit; Joost Rotteveel; Frank J. Snoek (Journal of Diabetes Research)
Introduction. Previous studies indicated an association between behavior problems (internalizing, externalizing) and glycemic control (HbA1c) in youth with type 1 diabetes (T1D). The aim of this study is to examine if this association is mediated by self-confidence and mismanagement of diabetes. Methods. Problem behavior was assessed with the Strengths and Difficulties Questionnaire. Mediating variables were assessed using the Confidence in Diabetes Self-Care-Youth and Diabetes Mismanagement Questionnaire. HbA1c was derived from hospital charts. Bootstrap mediation analysis for multiple mediation was utilized. Results. 88 youths with T1D, age 11–15 y, participated. The relation between both overall problem behavior and externalizing behavior problems and HbA1c was mediated through confidence in diabetes self-care and mismanagement (a1b1+a2b2  path; point estimate = 0.50 BCa CI 95% 0.25–0.85; a1b1+a2b2  path; point estimate = 0.73 BCa CI 95% 0.36–1.25). Conclusions. Increased problem behavior in youth with T1D is associated with elevated HbA1c and mediated by low self-confidence and diabetes mismanagement. Screening for problem behavior and mismanagement and assisting young patients in building confidence seem indicated to optimize glycemic control.